The natural hazard sector's engagement with Indigenous peoples: a critical review of CANZUS countries. (6th November 2018) - Thomassin, Annick; Neale, Timothy; Weir, Jessica K.
Abstract: Natural hazard management agencies across the settler countries Canada, Australia, Aotearoa New Zealand, and the United States (or CANZUS countries) are presently involved in an increasing range of collaborative and consultative engagements with Indigenous peoples. However, perhaps because these engagements are diverse and relatively recent, little has been written about how they emerged and, from these agencies' perspectives, little is known about how these engagements find their motivation within government natural hazard management frameworks. In this article, we review existing academic and grey literature to categorise the origins of recent and present engagements and then identify and elaborate on the key rationales informing natural hazard management agencies' interactions with Indigenous peoples. We argue both that the broad principles of sustainability and inclusion have transformed these interactions and that developmentalist approaches and an overemphasis on Indigenous peoples' traditional knowledge can sometimes undermine this work. Incorporating critiques of settler colonialism relevant to the CANZUS context, this review aims to support established, emerging, and future collaborative engagements by investigating and analysing the literature to date.